Profiling β Thalassemia Mutations in Consanguinity and Nonconsanguinity for Prenatal Screening and Awareness Programme - Ravindra Kumar; Vandana Arya; Sarita Agarwal (Advances in Hematology)
Mutation spectrum varies significantly in different parts and different ethnic groups of India. Social factors such as preference to marry within the community and among 1st degree relatives (consanguinity) play an important role in impeding the gene pool of the disease within the community and so in society by and large. The present paper discusses the role of consanguinity in profiling of beta thalassemia mutation, and thus the approach for prenatal screening and prevention based awareness programme. Clinically diagnosed 516 cases of beta thalassemia were screened at molecular level. A detailed clinical Proforma was recorded with the information of origin of the family, ethnicity, and consanguinity. The present study reports that subjects originating from Uttar Pradesh, Uttarakhand, Bihar, and Jharkhand have c.92+5G>C and c.124_127delTTCT mutation as the commonest mutation compared to the subjects hailing from Madhya Pradesh and Chhattisgarh and Nepal where sickle mutation was found more common. In 40 consanguineous unions more common and specific beta mutations with higher rate of homozygosity have been reported. This consanguinity-based data helps not only in deciding target oriented prenatal diagnostic strategies but also in objective based awareness programmes in prevention of thalassemia major birth.